CircGNG4 Promotes the Progression of Prostate Cancer by Sponging miR-223 to Enhance EYA3/c-myc Expression - Xu, Shengxian; Lian, Zhenpeng; Zhang, Siyang; Xu, Yong; Zhang, Hongtuan (Frontiers in Cell and Developmental Biology, 2021)
Patients diagnosed with prostate cancer often have a poor prognosis and limited treatment options, as the specific pathogenesis remains to be elucidated. Circular RNA (circRNA) is a type of non-coding RNA that interacts with microRNA (miRNA/miR) and transcription factors to regulate gene expression. However, little is known about specific circRNAs that serve roles in the pathogenesis of prostate cancer. Findings of the present study confirmed that circRNA G protein subunit γ 4 (circGNG4) was upregulated in prostate cancer tissues and cell lines. Knockdown of circGNG4 inhibited the malignant behavior of prostate cancer cells. Furthermore, bioinformatics were used to predict targeting interactions between circGNG4 or miR-223 and EYA transcriptional coactivator and phosphatase 3 (EYA3)/c-Myc mRNA. miR-223 inhibited the malignant behavior of prostate cancer cells, while EYA3/c-Myc had the opposite effect. circGNG4 enhanced the expression of EYA3/c-Myc by sponging miR-223 to promote the growth of prostate cancer tumors in vivo. In conclusion, the circGNG4/miR-223/EYA3/c-Myc regulatory pathway promoted the malignant progression of prostate cancer. The results of the present study may provide potential new targets for the diagnosis or treatment of prostate cancer.